2020
DOI: 10.1016/j.ijpsycho.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent generalization of conditioned responses to threat and safety signals

Abstract: Contextual information can modulate the conditioned response to a threat signal (conditioned stimulus, CS+): fear responses are either potentiated or attenuated depending on whether the context is threatening or safe. In this study, we investigated the influence of context on conditioned fear as well as on generalization of conditioned fear. Thirty-two participants underwent a cue-in-context learning protocol in virtual reality (VR). On Day 1 (acquisition), participants received a mild painful electric shock (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 65 publications
(116 reference statements)
0
7
1
Order By: Relevance
“…In contrast to the rodent literature, most human studies tested fear generalization shortly after fear acquisition (Dunsmoor, Kroes, et al, 2017;Holt et al, 2014;Lissek et al, 2008Lissek et al, , 2014Onat & Büchel, 2015). To the best of our knowledge, there are only two behavioral studies that explored fear generalization processes after a delay of 24 hr in humans (Andreatta et al, 2020;Dunsmoor, Otto, et al, 2017). Whereas one study focused on the influence of contextual information on fear generalization (Andreatta et al, 2020), another study suggested an increased level of fear generalization due to stress for older memories but not for recent memories, that is, a test of fear generalization after a 24-hr delay compared to an immediate test (Dunsmoor, Otto, et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the rodent literature, most human studies tested fear generalization shortly after fear acquisition (Dunsmoor, Kroes, et al, 2017;Holt et al, 2014;Lissek et al, 2008Lissek et al, , 2014Onat & Büchel, 2015). To the best of our knowledge, there are only two behavioral studies that explored fear generalization processes after a delay of 24 hr in humans (Andreatta et al, 2020;Dunsmoor, Otto, et al, 2017). Whereas one study focused on the influence of contextual information on fear generalization (Andreatta et al, 2020), another study suggested an increased level of fear generalization due to stress for older memories but not for recent memories, that is, a test of fear generalization after a 24-hr delay compared to an immediate test (Dunsmoor, Otto, et al, 2017).…”
mentioning
confidence: 99%
“…To the best of our knowledge, there are only two behavioral studies that explored fear generalization processes after a delay of 24 hr in humans (Andreatta et al, 2020;Dunsmoor, Otto, et al, 2017). Whereas one study focused on the influence of contextual information on fear generalization (Andreatta et al, 2020), another study suggested an increased level of fear generalization due to stress for older memories but not for recent memories, that is, a test of fear generalization after a 24-hr delay compared to an immediate test (Dunsmoor, Otto, et al, 2017). However, to what extent the neural underpinnings of immediate and delayed fear generalization differ is completely unknown.…”
mentioning
confidence: 99%
“…In studies on basic mechanisms of fear learning, there was either 1) no reporting of the results, 2) reporting that the results of self-measures were not significant, or 3) self-report measure scores were used to stratify participants into different analysis groups. For example, Andreatta et al (2020) (study ID = 2) reported administering the State Trait Anxiety Inventory (STAI) but made no use of score results in the analysis of results. Another study using healthy young adults as participants (Kroes et al (2017), study ID = 11) found no evidence of moderation of EMG scores by scores from the Trait section of the State Trait Anxiety Inventory (STAI-T), Intolerance of Uncertainty Scale (IUS), or Childhood Trauma Questionnaire, and explained this finding by pointing out that self-report measures scores for the healthy young adult population tend to be low and homogeneous.…”
Section: Coding and Analysis Protocolmentioning
confidence: 99%
“…On the other hand, cue‐in‐context conditioning studies suggest that contextual factors can modulate responding to conditioned fear cues (Andreatta & Pauli, 2021), by demonstrating stronger fear responses during a threatening compared with a safe context. However, in these studies, fear cues only predict aversive events if encountered in the threatening, but not in the safe context (Andreatta et al, 2020; Baas & Heitland, 2015; de Voogd et al, 2020). Thus, there is no independent induction of fear and anxiety that would be necessary to study their interaction.…”
Section: Introductionmentioning
confidence: 99%